A World of Flows—Labour Mobility, Capital and Knowledge in an Age of Global Reversal and Regional Revival, 3 rd – 6 th June 2018, Università della Svizzera Italiana, Lugano, Switzerland - noname nosurname; noname nosurname (Journal of Economic Sociology, 2018)
A World of Flows—Labour Mobility, Capital and Knowledge in an Age of Global Reversal and Regional Revival, 3 rd – 6 th June 2018, Università della Svizzera Italiana, Lugano, Switzerland